Isolated Interrupted Aortic Arch: Unexpected Diagnosis in a 63-Year-Old Male - Hassan Javadzadegan; Jahan Porhomayon; Alireza Sadighi; Mehrdad Yavarikia; Nader Nader (Case Reports in Critical Care)
A 63-year-old male with history of hypertension, dyspnea on exertion, and chronic chest pain was admitted for elective cardiac angiography. Arterial blood pressure was 160/90 mmHg in both arms. Femoral and popliteal pulses were extremely weak, and third (S3) and fourth (S4) heart sounds were audible. Aortography showed a mildly dilated aortic root with double brachiocephalic trunk and interruption of aortic arch at isthmus. Profuse and well-developed collaterals appeared at neck and thorax. The patient was recommended to take medical treatment for his hypertension and advanced heart failure. The aim of this paper, is to review the diagnostic and therapeutic options for treatment of the interrupted aortic arch.